The Influence of Accounting Conservatism, Ownership Concentration, and Debt Maturity on Investment Efficiency - rosalina, eka rosalina (AIBPM Publisher, 2024)
This study aims to examine the influence of accounting conservatism, ownership concentration, and debt maturity on investment efficiency. This research uses quantitative methods with multiple linear regression models using the SPSS program. The data used in this study are the annual financial statements of companies on the Indonesia Stock Exchange. The population in this study were 122 non-classical consumer companies listed on the Indonesia Stock Exchange. After purposive sampling, the final sample consisted of 42 companies so that the total sample was 126 data.. The results of multiple linear regression testing show support for the hypotheses of this study, namely: (1) the result of the influence of accounting conservatism on investment efficiency has a significant effect on investment efficiency, (2) the result of the influence of accounting conservatism on investment efficiency has a significant effect on investment efficiency, (2) the result of the influence of ownership concentration has a significant effect on investment efficiency, (3) the result of the influence of debt maturity has no effect on investment efficiency.Keywords: investment efficiency accounting conservatism, ownership concentration, debt maturityÂ